Role Ambigiguity Terhadap Work Female Employee Melalui Job Stress Sebagai Variabel Intervening (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
Covid-19 delivers change in a way comprehensive including sector economy . Indonesia experienced change significant . Current company this and rapid development _ demand Woman For take switch in develop career work , and even there is something to be leader organization . Different with the past placing perception Woman considered low and inclined experience discrimination in career and work . Opt-in Woman in Work bring negative consequences resulting from conflict role . Study This aim For know about connection between role ambiguity and Work Female Employee which is moderated by job stress . The analytical method used is multiple linear regression with the SPSS 21 program. Research sample Female employees in the district Majalengka , numbering 100 employees . The result role ambiguity influences negative towards Work Female Employees, Job stress influential negative in connection between role ambiguity and the next Work Female Employee Can made material study For study about Working Female Employees .